Heterogeneous Fenton-like degradation of phenanthrene catalyzed by schwertmannite biosynthesized using Acidithiobacillus ferrooxidans. Issue 35 (18th April 2017) - Meng, Xiaoqing; Yan, Su; Wu, Wenzhu; Zheng, Guanyu; Zhou, Lixiang
Abstract : Heterogeneous Fenton-like degradation of phenanthrene in aqueous solution was investigated using schwertmannite biosynthesized by Acidithiobacillus ferrooxidans LX5 as a catalyst. Abstract : Heterogeneous Fenton-like degradation of phenanthrene in aqueous solution was investigated using schwertmannite biosynthesized by Acidithiobacillus ferrooxidans LX5 as a catalyst. The effects of different reaction parameters including catalyst loading, H2 O2 concentration, initial solution pH and inorganic anions on the Fenton-like degradation of phenanthrene were studied. Results showed that the biosynthesized schwertmannite had an effective catalytic ability on phenanthrene degradation. The degradation efficiency of phenanthrene was 99.0% within 3–5 h reaction under conditions of H2 O2 200 mg L −1, schwertmannite 1 g L −1, phenanthrene 1 mg L −1 and pH 3.0–4.5. The degradation was mainly via a surface mechanism, in which phenanthrene was readily adsorbed on the surface of schwertmannite and then oxidized by ˙OH produced from H2 O2 decomposition. The XPS results of schwertmannite before and after Fenton-like degradation of phenanthrene revealed the change of Fe 2+ /Fe 3+ species on the surface of schwertmannite. Moreover, phthalates, octadecanoic acid and 9, 10-phenanthraquinone were identified by GC-MS analyses as the main intermediate compounds during phenanthrene degradation, and all the intermediates were finally mineralized. The repeated use of biosynthesized schwertmannite for phenanthrene degradation illustrated its stability and reusability as a Fenton-like catalyst. Therefore, schwertmannite biosynthesized using A. ferrooxidans is an excellent catalyst for the degradation of phenanthrene in heterogeneous Fenton-like reactions.